PENGARUH KETERLIBATAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN TERHADAP PEMULIHAN EKONOMI PASCA BENCANA BANJIR BANDANG KECAMATAN TANGSE KABUPATEN PIDIE - Rahmadi .; Azmeri .; Safrida . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
The purpose of this study was to determine the extent of the involvement of the National Program for Community Empowerment (PNPM) Rural and the impact of the economic recovery affected people in the district of Pidie District Tangse. This study was a qualitative descriptive with qualitative data. From the results of the study showed that in the rehabilitation and reconstruction of PNPM MP carry out the rehabilitation of road infrastructure of the village, where the execution is so effective is because the proposed initiative is a direct result of deliberation villagers (botton up) which aim to free movement and mobilize people to implement improvements economy damaged by the disaster. The perceived impact is accelerating the construction of village access roads improvements more quickly handled and can provide comfort for the user community. In addition to the pattern of labor-intensive, very enthusiastic people involved as day laborers, both men and women on such projects so as to increase financial income to cover economic needs.Keywords: Involvement PNPM MP, community development, accelerating of economic recovery, after the disaster